Reducing medication errors in critical care patients: pharmacist key resources and relationship with medicines optimisation. (4th January 2018) - Bourne, Richard S.; Shulman, Rob; Jennings, Jennifer K.
Abstract: Background: Medication errors are the most common type of medical errors critical care patients experience. Critical care units utilise a variety of resources to reduce medication errors; it is unknown which resources or combinations thereof are most effective in improving medication safety. Objectives: To obtain UK critical care pharmacist group consensus on the most important interventions/resources that reduce medication errors. To then classify units that participated in the PROTECTED UK study to investigate if there were significant differences in the reported pharmacist prescription intervention type, clinical impact and rates according to unit resource classification. Methods: An e‐Delphi process (three rounds) obtained pharmacist consensus on which interventions/resources were most important in the reduction of medication errors in critical care patients. The 21 units involved in the PROTECTED UK study (multicentre study of UK critical care pharmacist medicines interventions), were categorised as high‐, medium‐ and low‐resource units based on routine delivery of the final Top 5 interventions/ resources. High and low units were compared according to type, clinical impact and rate of medication interventions reported during the PROTECTED UK study. Key findings: Consensus on the Top 5 combined medication error reduction resources was established: advanced‐level clinical pharmacist embedded in critical care being ranked most important. Pharmacists working on units with high resources made significantly more clinically significant medicines optimisations compared to those on low‐resourced units (OR 3.09; P = 0.035). Conclusions: Critical care pharmacist group consensus on the most important medication error reduction resources was established. Pharmacists working on high‐resourced units made more clinically significant medicines optimisations.